2010
DOI: 10.1111/j.1475-3588.2009.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Child Community Psychology Services in the Community: Experiences from the NIPPERS Project

Abstract: Background:  The NIPPERS (Nursery Intervention Project for Parents & Education Related Services) was a novel community psychology service based in nursery settings in socio‐economically disadvantaged, inner‐city areas in London. Method:  The service included consultation work with nursery staff, structured parenting groups and individual sessions for parents. Results:  The delivery of the clinical service and research evaluation underwent several changes in the first phase of the project, in particular to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…Parents’ general support for screening is in keeping with other studies on school-based identification [50–55]. Two other UK-based studies on specific screening programmes also reported that parents found screening acceptable [54, 55], although one programme required modifications to enhance acceptability [55].…”
Section: Discussionsupporting
confidence: 65%
“…Parents’ general support for screening is in keeping with other studies on school-based identification [50–55]. Two other UK-based studies on specific screening programmes also reported that parents found screening acceptable [54, 55], although one programme required modifications to enhance acceptability [55].…”
Section: Discussionsupporting
confidence: 65%